A portable electrochemical microcell for weld inspection of duplex stainless steel tanks - Guilherme, L. H.; Benedetti, A. V. [UNESP]; Fugivara, C. S. [UNESP] (Association for Materials Protection and Performance (AMPP), 2019)
Electrochemical tests are well-established techniques used in corrosion studies, with the development of microcells and microcapillaries enabling localized evaluation of specific microregions of a welded joint. Until now, electrochemical studies using microcells have been performed exclusively in laboratories. Therefore, the present work presents a design of a portable electrochemical microcell for weld inspection, together with its application at an industrial site. The conceptual design and the detailed engineering of the device and its components are presented and discussed. A case study was undertaken while four aseptic tanks were being constructed from UNS S32101 lean duplex stainless steel, which was welded by a tungsten inert gas welding process with automatic feed of AWS ER2209 filler metal. The electrochemical behavior of the welded joint was evaluated by acquiring cyclic potentiodynamic polarization curves in 1 mol/L NaCl aqueous solution and double loop electrochemical potentiokinetic reactivation curves in 0.5 mol/L H 2 SO 4 + 0.01 mol/L KSCN aqueous solution, for microregions of the base metal, the fusion line, and the weld metal. The results demonstrated agreement between the electrochemical parameters obtained in the laboratory and at the industrial site, with both indicating that the fusion line was the microregion most susceptible to localized corrosion. Furthermore, crevice corrosion and leaks were not evidenced in the electrochemical tests at the industrial site. Therefore, storage tanks installed at an industrial site can be efficiently inspected using the portable electrochemical microcell presented in this study.
Keywords: Duplex stainless steel; Electrochemical tests; Localized corrosion; Portable electrochemical microcell; Storage tank; Welded joint